Peak runoff reduction through the use of various detention tank systems - Tok, Zhao Chin (2017)
As Singapore continues to develop, there will be an increase in the rainwater surface runoff, which will exceed the current drainage capacity. In order to tackle this potential problem, the Public Utilities Board (PUB) launched the Active, Beautiful, Clean (ABC) Waters Programme, hoping to encourage developers and consultants to implement ABC features into the design of new developments or upgrading of existing sites. According to the Code of Practice for Surface Water Drainage published by PUB, it is required by the law to provide surface water drainage for any development site greater than 0.20 hectares to control the peak runoff discharge from the site. Therefore, a study is carried out to investigate the most efficient way to reduce peak runoff by implementing on-site detention tanks using an excel spreadsheet. Through the use of excel spreadsheet; the preliminary design for the detention tank can be obtained effectively. It is important to understand that the excel spreadsheet is for planning purposes and the Qualified Person (QP) has to be responsible to ensure the accuracy of the result by developing the necessary hydraulic calculations using software such as the Storm Water Management Model (SWMM). This study includes findings on the optimum design of the detention tanks for various scenarios and looks into the relationship between the time of concentration and the size of detention tank.